Intraductal papillary mucinous neoplasm penetrating to the stomach, duodenum, and jejunum demonstrated on MR cholangiopancreatography with an oral negative contrast agent. Issue 1 (12th November 2012) - Tajima, Naoshi; Utano, Kenichi; Kijima, Shigeyoshi; Kawai, Akira; Fujita, Akifumi; Sakuma, Kazuya; Sugimoto, Hideharu; Fujii, Hirofumi
<x xml:space="preserve">Abstract</x> A 65‐year‐old man was referred to our hospital due to epigastric pain. Abdominal enhanced computed tomography (CT) demonstrated marked dilatation of the main pancreatic duct (MPD) and communication to the gastric and duodenal lumen was suspected. Esophagogastroduodenoscopy (EGD) showed a villous tumor with white mucous discharge in the posterior wall of the gastric corpus and duodenal bulb. Pathological specimens showed mucin‐producing epithelium with nuclear atypia that had developed in a papillary form. Based on these findings, we diagnosed intraductal papillary mucinous neoplasm (IPMN) arising in the MPD with penetration into the gastric and duodenal lumen. Magnetic resonance cholangiopancreatography (MRCP) with an oral negative contrast agent (manganese chloride tetrahydrate) showed a fistulous tract not only to the stomach and duodenum, but also to the jejunum. MRCP demonstrated mucous streaming with remarkably high intensity. In this case, an oral negative contrast agent was useful to distinguish mucous discharge from gastric fluid, facilitating the diagnosis of penetration to the jejunum. This finding was unobtainable by CT or EGD. When IPMN penetrating to other organs is suspected, MRCP with an oral negative contrast agent may provide important information. J. Magn. Reson. Imaging 2013;38:206–209. © 2013 Wiley Periodicals, Inc.